NUMERICAL MODELING OF DYNAMICS OF THE CROSS STRESSES CHANGE ALONG THE LENGTH OF ROUND INGOT IN MNLZ-3 - A. N. Chichko; V. A. Matochkin; D. V. Kukuj; A. V. Demin; G. I. Chichko (Литьë и металлургия)
The methods for calculation of cross pressures, formed at steel casting, in round ingot poured at MNLZ, allowing to take into account mechanical bend of ingot and thermal stresses, are offered. The dynamics of the thermal stresses along the length of ingot of circular section with diameter 160 mm and 240 mm of low-carbon steel St20 is established by means of computer modeling.